MEGA SPORTS EVENTS AND URBAN TRANSPORTATION AND MOBILITY: A CRITICAL VIEW OF RECENT URBAN INTERVENTIONS IN RIO DE JANEIRO CITY (GEOgraphia, 2022)
This article presents some of the main findings of the research project carried out by a group of Brazilians and Norwegian researchers during 2017, focusing on the so-called “legacies” of the 2014 and 2016 sporting mega-events held in Rio de Janeiro city, Brazil. The primary objective is to give an overview of the gap between discourse and reality provided by different social and political actors concerning the sporting mega-events in Rio de Janeiro, focusing on urban transportation and mobility. The main point is to evaluate the extent to which the public investments linked to urban mobility due to the mega sports events in Rio de Janeiro city have effectively improved the quality of life of the city dwellers. Thus, the Bus Rapid Transportation system, BRTs, and the new subway line that connects Barra da Tijuca neighborhood – the heart of the 2016 Rio de Janeiro Olympic Games, to the rest of the city were the primary means of urban transportation analyzed. Methodologically speaking, the main findings here are based on interviews with different social and political actors and articles, essays, and reports broadcast in the hegemonic and alternative media.